Template‐Directed Copying of RNA by Non‐enzymatic Ligation - Zhou, Lijun (John Wiley and Sons Inc., 2020)

(untitled) (Angew Chem Int Ed Engl)
The non‐enzymatic replication of the primordial genetic material is thought to have enabled the evolution of early forms of RNA‐based life. However, the replication of oligonucleotides long enough to encode catalytic functions is problematic due to the low efficiency of template copying with mononucleotides. We show that template‐directed ligation can assemble long RNAs from shorter oligonucleotides, which would be easier to replicate. The rate of ligation can be greatly enhanced by employing a 3′‐amino group at the 3′‐end of each oligonucleotide, in combination with an N‐alkyl imidazole organocatalyst. These modifications enable the copying of RNA templates by the multistep ligation of tetranucleotide building blocks, as well as the assembly of long oligonucleotides using short splint oligonucleotides. We also demonstrate the formation of long oligonucleotides inside model prebiotic vesicles, which suggests a potential route to the assembly of artificial cells capable of evolution.